Rethinking tribal culture and development - Ao, Adv. Imotemsu (New Delhi, 2011)
In tribal dominated area of our country, women from Bhil tribe came together to fight the liquor mafias. Alcoholism was making men in the community abdicate their responsibilities towards their families and indulge in domestic violence. The life of tribal woman is very tough, and they remain busy from dawn to dusk. The culture and lifestyle of tribals vary from place to place, but women enjoy a respectable status in their communities. The tribal people of India have been in contact with other people, that is the urban society, for a very long time and have been greatly influenced by them. There are still a few tribes in the Bastar district of the state of Madhya Pradesh, which are totally unaffected by any developmental programme. The Bhils, having once been a martial race, have a clear gender division of labour, which is not easily transgressed. The men, even if they want to help out at home, find it difficult to do domestic labour.
Keywords: Tribes-India-Social life and customs